School Choice and Higher Education Attainment - Diana Alessandrini; Joniada Milla (Institute of Labor Economics (IZA), 2022)
We analyze how school vouchers affect post-secondary attainment by exploiting the universal voucher program implemented in Chile in 1981. The program allowed students to choose which primary and secondary schools to attend. The government covered tuition independently of whether the chosen school was private or public. We find that vouchers increased the probability of attending PSE by 2-4 percentage points and the probability of PSE graduation by 1-3 percentage points. Students from low socio economic backgrounds benefited the most. Further, we study whether the impacts of vouchers depend on when school choice becomes available in a student's educational path. We find that the impacts of vouchers on PSE outcomes are maximized if vouchers are introduced before students start middle school.
Keywords: H43; I21; J31; 330; vouchers; school choice; higher education attendance